DOI: 10.31274/rtd-180813-9848
|View full text |Cite
|
Sign up to set email alerts
|

The development of the revised version of the Educational Outcome Expectancy Scale

Abstract: The quality of this reproduction is dependent upon the quality of the copy submitted. Broken or indistinct print, colored or poor quality illustrations and photographs, print bleed-through, substandard margins, and improper alignment can adversely affect reproduction. In the unlikely event that the author did not send a complete manuscript and there are missing pages, these will be noted. Also, if unauthorized copyright material had to be removed, a note will indicate the deletion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Instead of Eq. (3.2) a revised definition for broad resonances was used here: [18]. There is no clear assignment of 7 − and 9 − states to the 0 − band in [18]; the lowest tentative assignment was used.…”
Section: Bound and Quasi-bound State Properties Ofmentioning
confidence: 99%
“…Instead of Eq. (3.2) a revised definition for broad resonances was used here: [18]. There is no clear assignment of 7 − and 9 − states to the 0 − band in [18]; the lowest tentative assignment was used.…”
Section: Bound and Quasi-bound State Properties Ofmentioning
confidence: 99%
“…In general, one can read from the formalism of photoactivation with a constant production rate (which is approximately fulfilled in the above case), that the time until equilibrium is reached is a few times the lifetime of the unstable product. In the case of the 2 + state in 20 Ne at E x = 1634 keV the mean lifetime is τ = 1.05 ps [4]. Compared to the timescale of neon burning, which is of the order of years, thermal equilibrium is reached almost instantaneously.…”
Section: Discussionmentioning
confidence: 96%
“…Consequently the ratios of all observed resonances will be measured in one irradiation -provided that the ground-state branching ratios are well known. This might help to resolve minor discrepancies between the adopted resonance strengths in [4] and [2].…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analyses concerning the social cognitive career theory by Lent and colleagues (1994) presented earlier in the chapter showed that SE (Multon et al, 1991) and outcome expectancies (Young et al, 2004) were predictors of educational achievement. However, it appears that outcome expectancies do not predict academic grades in analyses in which SE is entered first in the regression equation (Lent et al, 1993;Tilley, 2002). …”
Section: Educational Achievementmentioning
confidence: 94%
“…Young and colleagues reported an effect size of .24 for outcome expectancies and subsequent mathematics grades. Studies examining the unique contribution of outcome expectancies after SE has been controlled for have found that only SE uniquely contributes to subsequent academic achievement (Lent, Lopez, & Bieschke, 1993;Tilley, 2002 (Krumboltz, Mitchell, & Jones, 1976;Mitchell & Krumboltz, 1990 focuses on how individuals learn from interactions with the environment in making career choices. It also tries to address the origin of career choice.…”
Section: Academic Performance Attainmentmentioning
confidence: 99%